The Role of Extrinsic Pathway (Death Receptor Pathway) Apoptosis through Caspase-8 in Atherogenesis due to High Fat and High Cholesterol Diet - Yanuartono Yanuartono; Hastari Wuryastuti; R Wasito; Sri Raharjo (Indonesian Food and Nutrition Progress, 2005)
Thirty male rats, strain Sprague Dawley were used as experimental animal to study the role of death receptor pathway apoptosis in atherogenesis due to high fat and high cholesterol diet. The rats were randomly alloted into three group (I, II, III) of 10 each. Group I as control was fed normal diet, group II was fed diet containing high fat diet, and group III was fed containing high fat and high cholesterol diet (atherogenic diet). After 6 and 12 weeks on experimental diet, 15 rats were selected randomly (5 rats of each group). All animal were then killed and the aorta were taken out for caspase-8 immunohistochemical analysis. Based on the present study result it can be concluded that high cholesterol and/or high fat diet induced apoptosis through death receptor pathway via caspase-8.